2023
DOI: 10.1177/09612033231206830
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning: Predicting hospital length of stay in patients admitted for lupus flares

Radu Grovu,
Yanran Huo,
Andrew Nguyen
et al.

Abstract: Background Although rare, severe systemic lupus erythematosus (SLE) flares requiring hospitalization account for most of the direct costs of SLE care. New machine learning (ML) methods may optimize lupus care by predicting which patients will have a prolonged hospital length of stay (LOS). Our study uses a machine learning approach to predict the LOS in patients admitted for lupus flares and assesses which features prolong LOS. Methods Our study sampled 5831 patients admitted for lupus flares from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Extreme Gradient Boosting (XGB) Algorithm is a machine learning one which can improve the integration of multiple decision trees by gradient boosting method, which is characterized by high accuracy, difficulty of adaptation and good scalability. Chen et al ( 24) indicated that the XGB algorithm was a suitable ML model for predicting length of hospital stay in ischemic stroke patients with high accuracy, less over-fitting and scalability and Grovu et al (35) showed that the XGB model has higher accuracy and better performance in predicting the length of hospitalization compared with other algorithms. Morgan et al (36) indicted that the accuracy and stability of ML models was improved and presented less over-fitting as the sample size increased and a more stable ML model in training and testing sets was necessary to be selected in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme Gradient Boosting (XGB) Algorithm is a machine learning one which can improve the integration of multiple decision trees by gradient boosting method, which is characterized by high accuracy, difficulty of adaptation and good scalability. Chen et al ( 24) indicated that the XGB algorithm was a suitable ML model for predicting length of hospital stay in ischemic stroke patients with high accuracy, less over-fitting and scalability and Grovu et al (35) showed that the XGB model has higher accuracy and better performance in predicting the length of hospitalization compared with other algorithms. Morgan et al (36) indicted that the accuracy and stability of ML models was improved and presented less over-fitting as the sample size increased and a more stable ML model in training and testing sets was necessary to be selected in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these larger reports used EMRs and administrative databases to identify patients with SLE, recognising that these types of data may be limited Review by diagnostic misclassification. [17][18][19][20][21] Many reports experienced 'class imbalance', where the SLE group sample size was considerably smaller compared with healthy controls, potentially biasing ML in favour of the more prevalent class. To address this, some reports used generative adversarial networks 22 23 and Synthetic Minority Oversampling TEchnique (SMOTE) 20 24 to generate synthetic data.…”
Section: Data Collectionmentioning
confidence: 99%